An analysis On Security Concerns and Their Possible Solutions in Cloud Computing Environment - Chandra, Naveen; Rastogi, Parag; Asthana, Amit (International Journal of Computer Sciences and Engineering, 2025)
Cloud computing offers services with much flexibility and very less infrastructure because of the distributed structure of cloud computing, this technology is used by an increasing number of end users. On the other hand, cloud computing presents an added level of risk because clouds are distributed in nature, so it becomes an easy targets for the intruders to exploit the vulnerabilities of the network. Therefore in this paper we have discussed the need of security mentioning different types of attacks which affect the availability, confidentiality and integrity of resources and services in cloud computing environment and suggested the cloud providers to protect the user data and information from inside or outside attacks by installing an intrusion detection and prevention system.